2021
DOI: 10.1007/s40291-021-00563-1
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Prevalence of Epidermal Growth Factor Receptor Mutations in Non-Small Cell Lung Cancer: A Meta-Analysis

Abstract: Background Identification of variable epidermal growth factor receptor ( EGFR ) gene mutations in non-small cell lung cancer (NSCLC) is important for the selection of appropriate targeted therapies. This meta-analysis was conducted to provide a worldwide overview of EGFR mutation and submutation (specifically exon 19 deletions, exon 21 L858R substitutions, and others) prevalence, and identify important covariates that influence EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 107 publications
2
54
2
1
Order By: Relevance
“…Wei et al [ 12 ] observed no significant differences in gender and smoking status between the two common mutations 19-Del and L858R. In a recent meta-analysis [ 5 ] for NSCLC patients worldwide, the percentage of male patients was a significant covariate for the overall EGFR mutation but not for the mutation subtypes. With the increase of the percentage of males, the EGFR mutation frequency decreased.…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wei et al [ 12 ] observed no significant differences in gender and smoking status between the two common mutations 19-Del and L858R. In a recent meta-analysis [ 5 ] for NSCLC patients worldwide, the percentage of male patients was a significant covariate for the overall EGFR mutation but not for the mutation subtypes. With the increase of the percentage of males, the EGFR mutation frequency decreased.…”
Section: Demographicsmentioning
confidence: 99%
“…The median ages were also comparable between the EGFR-mutated and wild groups [ 6 , 9 , 23 ]. In a recent meta-analysis, age was not considered as a covariate for the overall EGFR mutation [ 5 ]. Some studies take a different view on the relationship between EGFR mutations and age.…”
Section: Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In NSCLC, the incidence of EGFR mutations varies considerably in different regions of the world. Several studies reported that the prevalence of EGFR mutations ranged from 11% to 50% [ 30 , 31 ]. A large meta-analysis conducted in 2016 including 456 studies showed significant heterogeneity in all analyzed variables related to the prevalence of EGFR mutations in NSCLC patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR-activating mutations are typical for lung adenocarcinomas and are relatively frequent in nonsmokers, females, and East Asian patients. Common (classical) mutations, constituting up to 90% of EGFR mutations, include small in-frame deletions within exon 19 (codons 746-750) and a point mutation within exon 21 (L858R) (1). The remaining EGFR mutations (uncommon; non-classical) may be intrinsic (primary) or secondary, related to acquired resistance to EGFR TKIs (2)(3)(4).…”
mentioning
confidence: 99%